Time-kill kinetics of Piper betle L. ethanolic leaf extract on methicillin-sensitive Staphylococcus aureus - Lao, Ryan Christopher Co; Manglicmot Yabes, Ailyn (Life Sciences, Medicine and Biomedicine, 2023)
Staphylococcus aureus is one of the main pathogens in community and hospital infections that could cause mild skin infections to severe life-threatening bacteremia. Piper betle has shown antibacterial activities against S. aureus but its pharmacodynamics remains unclear despite its widespread availability in many over-the-counter preparations. This study aimed to describe the time-kill kinetics of P. betle extract against methicillin-sensitive Staphylococcus aureus ATCC 29213 (MSSA). Time-kill kinetics were conducted to describe the killing rate of P. betle extract by its effects on MSSA lag time duration, growth rate, and maximum optical density. The surviving colonies at different time-points after exposure to P. betle extract at minimum bactericidal concentration were also determined. Subinhibitory concentrations elucidated its concentration-dependent antibacterial activity by maintaining a trend of increasing lag time, decreasing growth rate, and decreasing maximum optical density as the concentration increases. In particular, concentration at 1250 μg/mL or 0.5 x minimum inhibitory concentration (MIC) showed consistent significant findings across these parameters. Concentrations at MIC and above did not show growth, indicating MSSA growth inhibition or death. P. betle extract’s bactericidal effect started immediately within two (2) hours and was sustained until no growth was observed from the eighth hour and beyond. P. betle extract maintained antibacterial activities against MSSA at subinhibitory concentrations and has also exhibited immediate and sustained bactericidal effect at minimum bactericidal concentration (MBC).